Castigo y Dolor: el Caso Sudamericano Hoy - Alfonso Donoso (Nuevo mundo - Mundos Nuevos, 2009)
This paper offers a critical analysis of the practice of punishment in South America in the 21st century. It undertakes this task through a series of steps: first, given the link between punishment and the imposition of pain and suffering, this article depicts criminal punishment as a morally problematic practice. Second, it briefly advances some of the most influential philosophical explanations of the connection between punishment and pain. Third, it describes the conditions in which imprisonment is currently applied in South America. And fourth, the article concludes that the practice of punishment in South America is not compatible with the normative principles advanced by the philosophy of punishment. Without the necessary amendments, punishment in South America amounts to the unjustified and unfair imposition of pain upon individuals.